Weekly water-loss from Spherical Water-loss Integrators on a Clearing and below Secondary Growth in Central Amazonia () - Brinkmann, W. L. F. (Acta Amazonica, 1972)
AbstractSpherical ceramic bulbs were set up as weekly water-loss integrators on a clearing and below a 2 year-old Cecropia-commumty at Km 18 of the Manaus-Itacoatiara Road. The instruments worked well in distinguishing the particular responses of individual sites to the impact of atmospheric agents as solar radiation, air temperature, air humidity and wind. Water-loss was primarily dependent on the order of magnitude of the weekly total of solar radiation and the presence or lack of a standing crop. Already a scarce secondary growth will reduce the weekly amount of water lost to the atmosphere considerably. Shelter-wood, however, considering the crop specific demands if introduced to tropical agriculture would provide favourable conditions as far as the impact of atmospheric controls on the tropical environment are concerned.